Evaluation of Appropriateness of A Nursing Intervention Program to Promote Pain Self-Management for Adult Outpatients with Cancer Pain - Masako Yamanaka; Kumi Suzuki (Elsevier, 2021)
Objective: This study aimed to develop a nursing intervention program structured to promote pain self-management for adult outpatients with cancer pain to enable coping with cancer pain-related problems and evaluate the appropriateness and clinical applicability of the program. Methods: A questionnaire survey was conducted with two pharmacists and ten oncology nursing specialists using a questionnaire created by the authors. The questionnaire comprised of 23 items asking about the appropriateness of the program, clinical applicability, and feasibility of instruction materials, rated by 5-point scales. Results: We collected 11 responses. The mean score of all the 23 items was 4.3 (standard deviation [SD] 0.6), the mean scores of the items were 4.4 (SD 0.6) for the appropriateness of the program, 4.2 (SD 0.5) for the clinical applicability of the program, and 4.3 (SD 0.7) for the feasibility of the instruction materials. The participants provided comments that the program made it easier to select patients for intervention and tasks that patients and nurses can share. Some comments pointed out that the program should be improved to allow patients who need the same intervention several times. Based on these comments, we modified the program partially and completed the first edition of the cancer pain self-management (CPSM) program. Conclusions: The findings suggest that the CPSM program may be considered appropriate and clinically applicable from the point of view of pharmacists and oncology nurses. Further studies are needed to verify the effects and usefulness of the program in clinical settings.